An Empirical Investigation of Investor’s Behavioral Biases on Financial Decision Making - Chhapra, Imran Umer; Kashif, Muhammad; Rehan, Raja; Bai, Ashow (Asian Journal of Empirical Research, 2018)
Investor’s irrationality is an inevitable reality that has been time and again highlighted by researchers (Statman, 2008). Therefore, this study is another effort to assess the role of behavioral biases in financial decision making in Pakistan Stock Exchange (PSX).A survey questionnaire is designed and used to collect responses using convenience sampling technique from sample of 250 investors of PSX. Behavioral biases include overconfidence, over thinking, herding, cognitive bias, and hindsight effect of investors. Multiple regression models are used to test influence of five behavioral biases on investment decision. The results show that overconfidence, over thinking, herding, cognitive bias, and hindsight effect have significant positive impact on investment decision. Overall results conclude that much change in investment decision is due to behavioral biases. This study will help financial advisors to better advice their clients. The one way to reduce these biases may be education and training of investors.